2021
DOI: 10.1007/s10661-021-09599-6
|View full text |Cite
|
Sign up to set email alerts
|

Land cover change and its implication to hydrological regimes and soil erosion in Awash River basin, Ethiopia: a systematic review

Abstract: significant positive interaction, while forest and water bodies had a substantial and slight negative relation to mean annual rainfall, respectively. Vegetation, bareland, urbanization, and agriculture/farmland are directly responsible for the hydrologic variation. LC change significantly affected hydrologic regimes and the distribution of spatial rainfall is correlated significantly to LC change pattern. Besides, due to the lack of LC management practices, the impact continues to propagate. Hence, this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…The Awash River is an important source of fluvial sediment to the Rift Valley. It is the second longest river in Ethiopia with a catchment area about 110,000 km 2 (Tola & Shetty, 2021). It transports material from the Ethiopian Highlands where it originates, through the Rift Valley to the lowland plain of the Afar Depression where it terminates in Abe Lake (Billi, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The Awash River is an important source of fluvial sediment to the Rift Valley. It is the second longest river in Ethiopia with a catchment area about 110,000 km 2 (Tola & Shetty, 2021). It transports material from the Ethiopian Highlands where it originates, through the Rift Valley to the lowland plain of the Afar Depression where it terminates in Abe Lake (Billi, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Elevation, drainage density, slope, and rainfall were classifed in accordance to get a uniform interval in between classes (Table 1). Similar research studies also applied uniform intervals to categorize classes for diferent factors [41][42][43][44]. Te land use type of the basin was condensed into fve classes such as forest, woodland, grass land, cultivated land, and water body where their level of infuences for food occurrence varies from very low, low, moderate, and high to very high, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recent history has shown that the basin is highly afected by recurrent foods as well as erosion [22,[39][40][41][42]. Increasing agricultural activities without land conservation and overgrazing leads to erosion and further aggravates fooding.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation of human-environment systems is seriously triggered by anthropogenic-related drivers, resulting in changes in landscape patterns [1]. The landscape functions have also been negatively affected by inappropriate remediation, industrialization, and urbanization activities, which have changed the hydrological cycle components, including waterways [1,2].…”
Section: Introductionmentioning
confidence: 99%